Transport and Recovery of Gilthead Sea Bream (Sparus aurata L.) Sedated With Clove Oil and MS222: Effects on Oxidative Stress Status - Teles, Mariana; Oliveira, Miguel; Jerez-Cepa, Ismael; Franco-Martínez, Lorena; Tvarijonaviciute, Asta; Tort, Lluis; Mancera, Juan M. (Frontiers in Physiology, 2019)
The use of anesthesia is a common practice in aquaculture to sedate fish and mitigate handling stress. Although the employ of anesthesia is considered beneficial for fish, as it reduces stress and improves welfare, at the same time it may induce hazardous side-effects. The aim of the present study was to investigate the effects of clove oil (CO) and tricaine methanesulfonate (MS222), two of the most used anesthetics, on several oxidative stress related parameters in gilthead sea bream (Sparus aurata), as these types of effects of anesthetics have been seldom investigated. To assess these effects, S. aurata juveniles were placed in a setup of mobile water tanks and were transported during 6 h with either 2.5 mg/L CO or 5 mg/L MS222. After transport, half of the fish were sampled, whereas the remaining fish were transferred to tanks without anesthetics where they were allowed to recover for 18 h before sampling. Changes in the expression levels of several target genes related with the antioxidant response and cell-tissue repair were evaluated in the gills, liver and brain. Those transcripts included glutathione peroxidase 1 (gpx1), catalase (cat), glutathione S-transferase 3 (gst3), glutathione reductase (gr), superoxide dismutase [Zn] (sod2), heat shock protein-70 (hsp70), and metallothionein (mt). Antioxidant enzymatic activities glutathione S-transferase, GST; catalase, CAT; and glutathione reductase, GR, levels of non-enzymatic antioxidants (non-protein thiols – NPT), and pro-oxidative damage, assessed as lipid peroxidation (LPO), were determined in gills, liver and brain. Acetylcholinesterase activity (AChE) was determined in plasma, gills, brain, muscle and heart as an indicator of neuro-muscular alterations. In plasma, the total antioxidant capacity (TAC) and total oxidative status (TOS) were also measured. Results showed that the use of both anesthetic agents, CO and MS222, interferes with fish antioxidant status. All tested biological matrices displayed alterations in antioxidant endpoints, confirming that these substances, although minimizing the effects of transport stress, may have long term effects on fish defenses. This result is of high relevance to aquaculture considering that the oxidative stress, may increase the susceptibility to different environmental or biotic stress and different types of pathologies.